The Effect of Hospitalization Education Given to the Parents of Premature Babies in Intensive Care Unit on Their Stress Levels - Sevda Doğru; Aysel Topan (Galenos Yayinevi, 2021)
Introduction:The study was planned as a semi-experimental type in order to evaluate the efficacy of hospitalization education given for decreasing stress levels of the parents whose babies were hospitalized in neonatal intensive care unit (NICU) and it was performed as a study including pre-test (before education) and post-test (after education) single group.Methods:Parents were made to see their babies for the first time before the education after getting informed consent from them; and they underwent "parent stress scale-NICU". Parents were given education with the guidance of "booklet for hospitalization education for parents-NICU" during the treatment, and the booklets were delivered to the parents at the end of the education.Results:When the mean scores of the parents from parent stress scale and its subscales were examined, it was detected that there was a statistically significant difference in total mean parent stress scale scores before and after the education at 1st and 2nd evaluations (p<0.05). It was also observed that there was a statistically significant difference between the subscales of "appearance and behaviors of the baby" and "relationship with the baby and parenting role" before and after the education at 1st and 2nd evaluations (p<0.05). However, no significant difference was found in the subscale of "images and sounds" before and after the education at 1st and 2nd evaluations (p>0.05).Conclusion:It was concluded that the hospitalization education given to decrease stress levels of the parents whose babies were hospitalized in NICU decreased the stress of the parents.